Playing it safe? Staff and young people's views about play opportunities in residential care - Lorraine McGuinness; Irene Stevens; Ian Milligan (Scottish Journal of Residential Child Care)
Play, in its widest sense, is the way that children and young people develop physically, socially and emotionally. Outdoor activities, in particular, fulfil a special role in the health and wellbeing of the child or young person. Pursuits such as picnics, visits to the beach, swimming and playing games should be a normal part of life for most children and young people, whether they are in a residential setting or living in a family home. Residential care has a high proportion of teenagers but children under twelve also form a significant part of the population (Milligan, Hunter and Kendrick, 2006). For teenagers the word 'play' is not necessarily one they would use themselves when it comes to describing social recreational activities such as visiting a park or a beach whether in the company of friends or carers. In the professional world of residential child care, however, outdoor 'play' is also referred to as outdoor activities.